Pendampingan Pembuatan Bahan Ajar Responsif Gender pada Guru-Guru Kelompok MGMP Bahasa Indonesia di Kabupaten Lombok Timur - Akmaluddin, Akmaluddin; Nurman, Muhammad (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2024)
This community-based community service article raises the topic of Assistance in Making Gender Responsive Teaching Materials for Teachers of the MGMP Indonesian Language Group in East Lombok Regency. This topic was raised on the basis that gender-responsive Indonesian language subject teaching materials are still limited. This community service activity aims to: (1) find out teachers' understanding of gender, (2) identify gender-biased textbooks, and (3) assist teachers in compiling gender-responsive teaching materials. This community service activity was carried out using the SL (service learning) method, an approach that combines community service activities with learning processes related to the programs or activities held. The results of the community service show that the participants gave a positive response to the community service activity, for example in the form of increased understanding of the concept of gender equality, increased ability to analyze gender-responsive teaching material content, and development of gender-responsive teaching material design skills. Thus, this community service activity contributes to increasing gender awareness among teachers and developing teacher competencies in compiling teaching materials